2018
DOI: 10.1007/s40140-018-0262-9
|View full text |Cite
|
Sign up to set email alerts
|

New Drug Developments for Neuromuscular Blockade and Reversal: Gantacurium, CW002, CW011, and Calabadion

Abstract: Purpose of ReviewThe purpose of this chapter is to provide a brief review of the literature on the recent developments in neuromuscular blockade and reversal agents.Recent FindingsNovel drug development resulted in pharmacological advancements in neuromuscular management and led to a new series of compounds, chlorofumarates, such as gantacurium, CW002, and CW011. These drugs have a fast onset and rapid to intermediate duration of action and can be rapidly reversed by l-cysteine adduction without side effects t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…However, after reviewing total 50 trials including 4,151 patients, the Cochrane Collaboration concluded that Sch is superior to rocuronium for RSI, as Sch could achieve acceptable intubating conditions faster (by 30-60 s) than rocuronium, thus rocuronium should be used as an alternative only in cases where Sch is contraindicated 82. Recently, another two new NMBAs (gantacurium and CW002) exhibit relatively rapid onset (90 s) and their neuromuscular blocking effect could be effectively reversed by cholinesterase inhibitors and cysteine 83, however they are not clinically approved yet and further studies need to be conducted to confirm their safety in humans 84. Therefore, Sch still plays an irreplaceable role as a NMBA in situations that require RSI and is still clinically used extensively in anesthesia around the globe.…”
Section: Discussionmentioning
confidence: 99%
“…However, after reviewing total 50 trials including 4,151 patients, the Cochrane Collaboration concluded that Sch is superior to rocuronium for RSI, as Sch could achieve acceptable intubating conditions faster (by 30-60 s) than rocuronium, thus rocuronium should be used as an alternative only in cases where Sch is contraindicated 82. Recently, another two new NMBAs (gantacurium and CW002) exhibit relatively rapid onset (90 s) and their neuromuscular blocking effect could be effectively reversed by cholinesterase inhibitors and cysteine 83, however they are not clinically approved yet and further studies need to be conducted to confirm their safety in humans 84. Therefore, Sch still plays an irreplaceable role as a NMBA in situations that require RSI and is still clinically used extensively in anesthesia around the globe.…”
Section: Discussionmentioning
confidence: 99%
“…Compounds belonging to these subgroups also exhibit varying additional activities. This classification is presented in Table 2 [1][2][3][24][25][26][27][28][29][30][31]. Aminosteroid drugs can induce vagolytic activity, leading to tachycardia and hypertension.…”
Section: Characteristic Of Non-depolarizing Muscle Relaxantsmentioning
confidence: 99%
“…Hence, this potential drug combination has attracted attention as a possible alternative to succinylcholine [ 81 , 82 ]. In addition, calabadion, a new antagonist of benzylisoquinoline-based neuromuscular blocking agent, and a combination of gantacurium (CW002) and L-cysteine are anticipated to become part of future ECT procedures [ 83 ].…”
Section: Drugs For Ectmentioning
confidence: 99%